Iron and ferroptosis in kidney disease: molecular and metabolic mechanisms - Wang, Wenjie; Chen, Jingdi; Zhan, Liying; Zou, Handong; Wang, Lu; Guo, Mengmeng; Gao, Hang; Xu, Jing; Wu, Wei (Frontiers in Immunology, 2025)
Maintaining iron homeostasis is necessary for kidney functioning. There is more and more research indicating that kidney disease is often caused by iron imbalance. Over the past decade, ferroptosis’ role in mediating the development and progression of renal disorders, such as acute kidney injury (renal ischemia-reperfusion injury, drug-induced acute kidney injury, severe acute pancreatitis induced acute kidney injury and sepsis-associated acute kidney injury), chronic kidney disease (diabetic nephropathy, renal fibrosis, autosomal dominant polycystic kidney disease) and renal cell carcinoma, has come into focus. Thus, knowing kidney iron metabolism and ferroptosis regulation may enhance disease therapy. In this review, we discuss the metabolic and molecular mechanisms of iron signaling and ferroptosis in kidney disease. We also explore the possible targets of ferroptosis in the therapy of renal illness, as well as their existing limitations and future strategies.